Development of 2D and 3D Quantitative Structure Activity Relationship Models of Thiazole Derivatives for Antimicrobial Activity (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
A series of 20 molecules of Aryl Thiazole derivatives reported in literature Khan M S et al (2009) were used for development of 2D and 3D quantitative structure activity relationship (QSAR) models. The data set of 20 molecules were divided into training and test set in the ratio of 70:30, The biological activity was converted to logarithmic scale (pIC50) in mathematical operation mode of the software. The statistically significant 2D-QSAR models for G+ inhibition activity are r2 =0.9521 and q2 = 0.8619 and 3D QSAR results for internal (q2 = 0.8283,) and external (predictive r2 = 0.4868,) validation criteria. Thus, 3D QSAR models showed that electrostatic effects at the area of [E_685 (-10.00-0.10.00)+E_460(-0.4530-0.273)+E_531(-0.6212-0.2506)]dominantly determine the binding affinities. 2D QSAR studies revealed that T_C_C_4 descriptors were major contributing descriptor in case of G+ inhibition activity. 3D QSAR Methods were performed using kNN-MFA method. The results derived may be useful in further designing novel more potent agents.